Digital Transformation and Financial Strengthening for Village-Owned Enterprises to Accelerate Inclusive and Sustainable Rural Development - Hayatie, Marliza Noor; Nadiar, Rahmi; Bandi, Maulida Hirdianti; Hidhayati, Annisa Tri; Alfikri, Rahmatullah (Universitas Lambung Mangkurat, 2025)
This community service program aimed to strengthen the economic foundation of Guntung Besar Village by empowering its Village-Owned Enterprise (BUMDes) Mandiri Sejahtera through professional financial and digital marketing management. The program addressed problems such as the absence of standardized financial records, limited digital marketing skills, and a lack of product legality, like BPOM certification. The methods included participatory approaches, such as socialization, training in digital bookkeeping and e-commerce platforms (Tokopedia, Shopee, TikTok Shop), content creation, and assistance with BPOM registration. This community service program aimed to strengthen the economic foundation of Guntung Besar Village by empowering its Village-Owned Enterprise (BUMDes) Mandiri Sejahtera through digital transformation and financial literacy. The program addressed issues such as unstandardized bookkeeping, limited digital marketing skills, and a lack of product legality (BPOM). Activities included participatory training on Google Sheets, e-commerce platforms (Tokopedia, Shopee, and TikTok Shop), branding design, and assistance with BPOM applications.